Հայոց դարձի առաջին փուլը քաղաքական դիտանկյունից - Սարգսյան, Աշոտ
The adoption of Christianity as state religion in the Roman Empire, given the complexity and seriousness of the problem, was a gradual and careful political process that lasted about a century and involved a lengthy and detailed discussion and strategy in advance. Having spent a long time in Roman political circles, Trdat should have been familiar with his strategy in this direction. King Tirdat III of Armenia immediately took the same political step as a revolutionary act, dictated by external challenges that threatened statehood and pressing internal problems that required solutions. With the adoption of Christianity, Trdat sharply separated from Sasanian Persia (which declared Zoroastrianism as the state religion and claimed power over Armenia through its spread), but not from the Roman Empire, as it is interpreted in modern historical works. Despite the fact that the paths and methods of adopting Christianity in the Roman Empire and in Armenia were diametrically different, in both cases they were the result of precise political calculations determined by the peculiarities of the given country and the primary agenda of the state. Trdat’s decision was bold not only because he was the first in the world, but also from the point of view of overcoming the resistance of all social strata, given the inertia of thousand-year-old pagan traditions. The adoption of Christianity in Armenia occurred in two stages, each of which lasted about a century. The revolutionary beginning of the first stage was the proclamation of Christianity as state religion in the early 4th century, and the beginning of the second stage was the creation of the Armenian written language about a century later. Correction, coordination and political interpretation of the realities of the first stage are a necessary basis for recognizing and assessing the motives and foundations of the emergence of the “golden age” after the creation of the Armenian writing as a means of serving the primary political task of the agenda of that time. Принятие христианства в качестве государственной религии в Римской империи было постепенным политическим процессом, который длился около столетия и предполагал заранее подробно продуманную и осторожную стратегию. Находясь долгое время в политических кругах Рима, Трдат с этой стратегией должен был быть знаком. В Армении царь Трдат III сразу же предпринял такой же политический шаг. Это был революционный акт, продиктованный как внешними угрозами для государственности, так и насущными внутренними проблемами. С принятием христианства Трдат резко отделился от Сасанидской Персии (которая объявила зороастризм государственной религией и претендовала на власть над Арменией через его распространение), но не от Римской империи, как это интерпретируется в современных исторических работах. Несмотря на то, что пути и методы принятия христианства в Римской империи и в Армении диаметрально различались, они в обоих случаях были результатом точных политических расчётов, обусловленных особенностями данной страны и первоочередной повесткой дня государства. Решение Трдата было смелым не только потому, что оно был первым в мире, но и с точки зрения преодоления сопротивления всех социальных слоев, инерции тысячелетних языческих традиций. Принятие христианства в Армении происходило в два этапа, каждый из которых длился около столетия. Революционным началом первого этапа стало провозглашение этой религии государственной в начале IV века, а началом второго этапа стало создание армянской письменности примерно столетием позже. Политическая интерпретация реалий первого этапа является необходимой основой для определения причин возникновения «золотого века» после создания армянской письменности – средства, обслуживающего первоочере- дную политическую задачу того времени.
Keywords: Պատմաբանասիրություն